Inhibiting vascular smooth muscle cell proliferation mediated by osteopontin via regulating gut microbial lipopolysaccharide: A novel mechanism for paeonol in atherosclerosis treatment - Shi, Xiaoyan; Wu, Hongfei; Liu, Yarong; Huang, Hanwen; Liu, Ling; Yang, Yulong; Jiang, Tingting; Zhou, Min; Dai, Min (Frontiers in Pharmacology, 2022)
BACKGROUND Although the gut microbiota are involved in metabolic disease such as atherosclerosis, the underlying mechanism remains elusive. Paeonol (Pae) is a natural phenolic compounds isolated from Cortex Moutan, which exhibits anti-atherosclerosis effects. Our previous research demonstrated that gut microbiota as a site of Pae action. However, the mechanism by which Pae exerts its anti-atherosclerotic effect through regulation of gut microbiota remains unclear.. OBJECTIVE To investigate a potential mechanistic link between the gut microbial lipopolysaccharide (LPS) and vascular smooth muscle cells (VSMCs) proliferation in atherosclerosis progression, and explored the possible role of Pae. METHODS Experimental atherosclerosis was established in ApoE-/- mice, and the atherosclerosis mice were treated with Pae for 4 week before sacrifice for analyses, while conducting fecal microbiota transplantation (FMT). Plaque area, levels of serum LPS, expressions of inflammatory factors in serum or aorta, and intestinal barrier permeability were determined. VSMCs were co-cultured with THP-1 cells. CCK8 assay and EdU staining were performed to assess the proliferative capacity of VSMCs. Immunofluorescence staining to observe the nuclear transfer of p65. Western blotting was used to detect candidate protein expression level, and quantitative real-time PCR (qRT-PCR) was used to detect the mRNA expression level in tissues or cells of each group. RESULTS During atherosclerosis progression, gut dysbiosis leads to the peripheral accumulation of gut microbial LPS, which as a trigger to stimulate osteopontin (OPN) production from circulating monocytes, inducing cell-to-cell crosstalk to promote VSMCs proliferation in aorta. Importantly, the elevation of LPS and OPN concentrations in the blood were also observed in patients with atherosclerosis. Pae could significantly improve atherosclerosis, suppress gut microbial LPS accumulation, inhibit monocyte/macrophages activation and VSMCs proliferation. CONCLUSIONS The present study provides a mechanistic scenario for how long-term stimulation of gut microbial LPS in circulating blood generates a pathological secondary response that leads to abnormal proliferation of VSMCs through high OPN expression in circulating monocytes, and suggest a novel strategy for atherosclerosis therapy by remodelling the gut microbiota.